Pengaruh Likuiditas, Profitabilitas, Ukuran Perusahaan, dan Kepemilikan Saham Publik terhadap Pengungkapan Laporan Tahunan Pada Perusahaan Property dan Real Estate yang Terdaftar Pada Bursa Efek Indonesia Tahun 2016-2019 - Elisa Yang; Pearlren Wijaya; Aurellia Sarikho; Thevania Gladystella; Maya Sabirina Panggabean (Ekonomis: Journal of Economics and Business, 2021)
This research aims to determine the Effect of Liquidity, Profitability, Company Size, and Public Share Ownership on Disclosure of Annual Reports on Property and Real Estate Companies Listed on the Indonesia Stock Exchange. The data used is sourced from the annual financial statements on the Indonesia Stock Exchange in 2016-2019. And there has been a selection based on the criteria that have been determined. The population used in the study was 50 companies and the sample used amounted to 21 companies. The technique in selecting a sample is to use the Purposive Sampling technique. The study used multiple linear regression analysis methods. From this study showed that Liquidity and Profitability had no significant effect on the Annual Report Disclosure Index on Property and Real Estate Companies Listed on the Indonesia Stock Exchange because the partial test results on liquidity variables negatively 0.01 percent and significant value positive effects 0.9 percent and partial test results on profitability variables negatively 1.4 and significant value positive influence 0.1 percent which proving not always the level of liquidity and profitability of the company will have a positive effect on the disclosure report. While the Size of the Company and Public Share Ownership have a significant influence on the Annual Report Disclosure Index on Property and Real Estate Companies Listed on the Indonesia Stock Exchange because the partial test results on the company's size variables positively affect 2.1 percent and significant value negatively affect 0.03 percent and partial test results on public share ownership variables positively affect 3.6 percent. But all variables have an simultaneous effect on the Annual Report Disclosure Index on Property and Real Estate Companies Listed on the Indonesia Stock Exchange.